Drum bits of terror - Abala, Imali J. (Langaa RPCIG, 2014)
Poignant and perceptive, Drum Bits of Terror tells the story of Samuel Adooli, a young man struggling to find his place in society. Inadvertently learning he was not born of wedlock, a cultural taboo, he embarks on his pursuit to find his father. He hits a roadblock as his quest side-tracks his schooling; he flunks his fourth form exams, leaving him with little to no option, but join a polytechnic college. Along the way, he forges a couple of unstable friendships, resulting in his assault not only once, but twice. Soon, his life becomes endangered when he finds himself entangled in an ethnically charged quagmire that threatens to down the stability of his nation. Ultimately, his survival becomes suspect and his choices startling. The realism in this story is exquisite.